Implementasi Pendidikan Implementasi Pendidikan Akal dalam Kurikulum Pendidikan Agama Islam Pada Tingkat Sekolah Dasar - Elmainetty, Harni; Arfian, Arfian - (Peneliti.net, 2023)
In Alquan, there are 49 repetitions that discuss 'aql, except for one, all of which are in the form of fi'il mudhar, especially material related to Wavu Jama'ah such as ta'qilun or ya'qilun. The verb ta'qilun is repeated 24 times and the verb ya'qilun is repeated 22 times. Although the verbs 'aqala, na'qilu and ya'qilu appear once each Reason is not just the power of the mind, the combination of all the powers of man which prevent him from falling into sin and error. That is why the Qur'an calls it the word